2011
DOI: 10.1182/blood-2010-12-326322
|View full text |Cite
|
Sign up to set email alerts
|

First report of multiple CEBPA mutations contributing to donor origin of leukemia relapse after allogeneic hematopoietic stem cell transplantation

Abstract: Donor cell leukemia after allogeneic hematopoietic stem cell transplantation might provide a unique human model for our understanding of leukemogenesis in vivo. We hypothesized that the "2-genetic-hits model" may contribute to the "leukemization" of donor cells and first evaluated these genetic mutations that are implicated in the development of acute myeloid leukemia in a donor cell leukemia patient and donor. The patient and his donor-sister both harbored a germline mutation in CEBPA (584_589dup). Susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 17 publications
1
46
1
Order By: Relevance
“…Indeed, this is further supported by the observation of a switch from normal to highly abnormal post-SCT of the patient's karyotype and FISH analysis. This supports the theory that in donor origin leukemia, the host environment in which the original malignancy developed could trigger an oncogenic process in donor cells, favored by the immunosuppressive status after transplantation, especially because the donor is still healthy [31,32]. …”
Section: Discussionsupporting
confidence: 77%
“…Indeed, this is further supported by the observation of a switch from normal to highly abnormal post-SCT of the patient's karyotype and FISH analysis. This supports the theory that in donor origin leukemia, the host environment in which the original malignancy developed could trigger an oncogenic process in donor cells, favored by the immunosuppressive status after transplantation, especially because the donor is still healthy [31,32]. …”
Section: Discussionsupporting
confidence: 77%
“…Inadvertent transplantation with stem cells from a sibling donor carrying an unrecognized germline predisposition syndrome can lead to devastating complications including failure to engraft, severe transplant-related toxicity, and the development of donor-derived leukemia [2630]. Longer term implications of having an underlying predisposition syndrome frequently include an increased risk of non-hematologic malignancies, particularly in disorders such as Fanconi Anemia (FA) and Dyskeratosis Congenita (DC) [22,31,32].…”
Section: When Why and How To Suspect And Evaluate For An Mds/aml Prmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Studies of large series of normal-karyotype AML have reported a frequency of CEBPA mutation of 8% to 13% 4,8,14 ; among these, 7% to 11% have germline CEBPA mutations. 4,8 The majority of the AML patients have 2 CEBPA mutations with both N-terminal frameshift mutation and C-terminal inframe mutation on different alleles.…”
Section: Aml With Germline Cebpa Mutationmentioning
confidence: 99%